2015
DOI: 10.1074/jbc.m114.623504
|View full text |Cite
|
Sign up to set email alerts
|

Annular Anionic Lipids Stabilize the Integrin αIIbβ3 Transmembrane Complex

Abstract: Background: Anionic lipids compete for electrostatic interaction in membrane proteins. Results: Despite competition, anionic lipids stabilize the integrin ␣IIb␤3 transmembrane complex. Conclusion: Stabilizing anionic lipid-protein interactions exist and supersede destabilizing effects. Significance: Anionic lipid-mediated stabilization of membrane proteins may be of a general nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…First, we performed unbiased microsecond-long MD simulations at the atomistic level in explicit solvent and an explicit lipid bilayer on the three TMDs, likely the currently most accurate way to explore structure and dynamics of transmembrane proteins 73 . The length of our MD simulations surpasses comparable previous ones on integrin TMDs by at least one order of magnitude 51 , 74 , 75 . We performed triplicate MD simulations for each system, which allows probing for the influence of the starting conditions and determining the significance of the computed results by statistical testing and rigorous error estimation 46 .…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…First, we performed unbiased microsecond-long MD simulations at the atomistic level in explicit solvent and an explicit lipid bilayer on the three TMDs, likely the currently most accurate way to explore structure and dynamics of transmembrane proteins 73 . The length of our MD simulations surpasses comparable previous ones on integrin TMDs by at least one order of magnitude 51 , 74 , 75 . We performed triplicate MD simulations for each system, which allows probing for the influence of the starting conditions and determining the significance of the computed results by statistical testing and rigorous error estimation 46 .…”
Section: Discussionmentioning
confidence: 41%
“…In agreement with ref. 51 , the R995-D723 salt bridge dissociates intermittently, as indicated by occupancies ≪100%. However, the MD simulations reveal that, among all four possible salt bridges that can form in the membrane-proximal region, R995-D723 is the most prevalent interaction, followed by R995-E726, and R997-E726 is the least prevalent one.…”
Section: Resultsmentioning
confidence: 99%
“…Based mostly on studies of the αIIbβ3 integrin it has been widely assumed that the TM/CT of β integrins have an intrinsic affinity for the corresponding domains of their cognate α subunits, such that they will form constitutively inactive heterodimers. Many studies have shown the isolated αIIb and β3 TM associate to form heterodimers in model membranes or as fusion proteins in E. coli or model cell lines (Lau et al, 2009; Berger et al, 2010; Partridge et al, 2005; Zhu et al, 2010; Schneider and Engelman, 2004; Schmidt et al, 2015; Lokappa et al, 2014; Kim et al, 2009). We observed similar results for heterodimerization of the α5 and β1 TM/CT, an observation consistent with evidence that this particular β1 integrin is activated according to the canonical model (Takagi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“… a Measurements performed in 43 mM DHPC, 17 mM POPC, 25 mM NaH 2 PO 4 /Na 2 HPO 4 pH 7.4 solution at 28 °C (effective bicelle q-factor of 0.5). b ΔΔG°,′ = (ΔG° αIIb β3,mutant −ΔG° αIIb β3 ) − (ΔG° αIIb β3(A711P),mutant −ΔG° αIIb β3(A711P) ) c Measured previously by competitive binding experiments 32 , resulting in larger experimental uncertainties than direct measurements. …”
Section: Figurementioning
confidence: 99%
“… c Measured previously by competitive binding experiments 32 , resulting in larger experimental uncertainties than direct measurements. …”
Section: Figurementioning
confidence: 99%